Evaluation of gastric emptying by means of scintigra-phy using different test meals - Viviana Montoya; Viviane Parisitto; Mateus Fontes; Luiz Gonzaga; Luciene das Graças; Arnaldo Prata (Brazilian Journal of Radiation Sciences, 2019)
Gastroparesis is a disorder characterized by symptoms and evidence of delayed gastric emptying (GE) in the absence of mechanical obstruction. Scintigraphy has been considered a "gold standard" for measuring Gastric Emptying Time (GET) and retention percentage of radio-labeled food, after four hours of ingestion. To obtain the images, it is recommended, worldwide, the use of the Tougas diet (255kcal) as a standard meal. The objective of this study was to compare the GET and the percentage of retention in the time of 4 h, obtained by scintigraphy using the Tougas diet (255 kcal) and the proposed diet (319 kcal). Thirty patients, both genders, aged 23 to 76 years,  were selected, they presenting clinical symptoms suggestive of gastroparesis. These parameters were measured for the same patient, but in different days. The results showed that the diet fat content used to obtain EG of solid foods by scintigraphy did not influence the retention percentage results after 4 hours of ingestion of the radiolabeled food. However, the time of two hours is an important parameter to be observed in the result of this examination. In addition, the data suggest that the proposed diet may be more efficient for the classification of the severity of EG delay in patients with clinical signs suggestive of gastroparesis.